Hot water recovery and reuse in textile sector with pilot scale ceramic ultrafiltration/nanofiltration membrane system. (20th May 2020) - Ağtaş, Meltem; Yılmaz, Özgün; Dilaver, Mehmet; Alp, Kadir; Koyuncu, İsmail
Abstract: This work is being conducted by real wastewater from disperse printing and reactive printing washing baths hot discharges mixing point and it was aimed to be treated and hot water recovery and reuse in the plant was targeted. For this purpose, pilot scale ceramic ultrafiltration/nanofiltration membrane system was used. In first ten cycle, ultrafiltration + nanofiltration membranes and in last four cycles only nanofiltration membrane was used. All samples were subjected to chemical oxygen demand, total hardness, total organic carbon, color and conductivity tests. Flux and temperature were also monitored throughout operations. According to obtained results, for ultrafiltration + nanofiltration cycles overall average removal efficiencies are 89%, 83.5%, 86.4% and 68% for chemical oxygen demand, color, total organic carbon and hardness, respectively. For only nanofiltration cycles, overall average removal efficiencies are 90.1%, 82.2%, 76.8% and 82% for chemical oxygen demand, color, total organic carbon and total hardness, respectively. Besides, treated wastewater was tested whether it is suitable for dyeing processes or not. And according to temperature difference between inlet and outlet streams, it can be said that it is feasible to use ceramic membrane technology for hot wastewater recovery and reuse. Highlights: Pilot scale ceramic UF/NF membrane system was used to treat hot textile wastewater. Applicability of ceramic membrane technology for hot water recovery was seen. Treated wastewater reusability in the plant was investigated. Dyeing experiments with treated hot wastewater was conducted on fabric. Cost analysis was performed.